Treatment and nursing of a lung cancer patient with chemotherapy-induced constipation based on the theory of removing obstruction (基于“通法”理论治疗1例肺癌化疗后便秘患者的护理体会) - LI Hui (李慧); HUANG Jinlan (黄金兰); JIA Xue (贾雪) (中西医结合护理, 2023)
This paper summarized the treatment and nursing of a lung cancer patient with chemotherapy-induced constipation based on the theory of removing obstruction. Comprehensive nursing interventions on diet, exercise, medication and daily life were carried out. Comprehensive green nursing techniques including massage, Traditional Chinese Medicine hot compress, auricular acupoint pressing, Wentong scraping and Tongfu herbal oil were applied to improve the bowl function and clinical symptoms of constipation caused by chemotherapy. (本文总结1例基于中医“通法”理论治疗肺癌化疗后便秘患者的护理经验。在饮食指导、运动干预、药物干预、生活护理等常规护理的基础上, 基于中医“通法”理论, 采用按摩、中药热奄包、耳穴贴压、温通刮痧联合通腑药油肿瘤绿色调护技术, 有效促进患者胃肠蠕动, 改善患者辨证症状, 有助于提高其生活质量。)